Linking Global Context of Sustainable Recovery with a Local Context Post-tsunami Recovery at Banda Aceh city, Indonesia - Ella Meilianda; Safrida Safrida; Yulia Yulia Direzkia (International Journal of Disaster Management, 2017)
The present study examines the recovery progress that has been achieved so far a decade after the tsunami disaster occurred in Banda Aceh city of Indonesia. Assessment of the recovery progress for several activities at the local context associated with the long-term disaster recovery phase include the hazard source control and area protection, land-use practices, mental health recovery, and economic development were conducted to identify windows of opportunities in different sectors to build back better. The findings subsequently situated within the framework of global context, by setting up a global framework linking the common targets between the Sendai Framework for Disaster Risk Reduction (SFDRR) and the Sustainable Development Goal (SDG). Among investigated sectors, the hazard source control, area protection and land-use practices seemed to miss the opportunity of changing the coastal areas to become more resilient to tsunami disaster, due to unsynchronized city masterplan with housing development towards the coastline. While this practice rather discouraging for promoting the idea of ‘build back better’, the other sectors such as community economic revitalization and mental health programs were rather successful in seizing the opportunities at different levels. It requires high commitment from different actors during the recovery to identify and grab the opportunities at the earliest phase of the recovery and to be able to coordinate and formulate the appropriate recovery programs that linked to the targets for sustainable development in the global context.